Parosteal osteosarcoma dedifferentiating into telangiectatic osteosarcoma: importance of lytic changes and fluid cavities at imaging - Azura, M.; Vanel, D.; Alberghini, M.; Picci, P.; Staals, E.; Mercuri, M. (2009)
PURPOSE: This study was performed to assess the imaging findings in cases of parosteal osteosarcoma dedifferentiated into telangiectatic osteosarcoma. Parosteal osteosarcoma is a low-grade well-differentiated malignant tumor. Dedifferentiation into a more aggressive lesion is frequent and usually visible on imaging as a central lytic area in a sclerotic mass. Only one case of differentiation into a telangiectatic osteosarcoma has been reported. As it has practical consequences, with a need for aggressive chemotherapy, we looked for this rather typical imaging pattern. MATERIALS AND METHODS: Review of 199 cases of surface osteosarcomas (including 86 parosteal, of which 23 were dedifferentiated) revealed lesions suggesting a possible telangiectatic osteosarcoma on imaging examinations in five cases (cavities with fluid). Histology confirmed three cases (the two other only had hematoma inside a dedifferentiated tumor). There were three males, aged 24, 28, and 32. They had radiographs and CT, and two an MR examination. RESULTS: Lesions involved the distal femur, proximal tibia, and proximal humerus. The parosteal osteosarcoma was a sclerotic, regular mass, attached to the cortex. A purely lytic mass, partially composed of fluid cavities was easily detected on CT and MR. It involved the medullary cavity twice, and remained outside the bone once. Histology confirmed the two components in each case. Two patients died of pulmonary metastases and one is alive. CONCLUSION: Knowledge of this highly suggestive pattern should help guide the initial biopsy to diagnose the two components of the tumor, and guide aggressive treatment.